Aggressive behavior in Indonesian football: Relationship between attitudes towards the field referee’s leadership and team cohesiveness - Akbar, Amin; Abd Karim, Zulakbal; Handrianto, Ciptro; Kurniawan, Rizal; Rinaldi, Rinaldi (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study examined the aggressive tendencies of Indonesian professional football players, and the relationship between team cohesion and views of referee leadership. Also, the study looked at referee leadership’s views from the perspective of team cohesiveness. The relational model was used as the foundation for the survey carried out as part of this investigation. Ninety professional football players from Indonesia’s Liga Satu Gojek-Traveloka participated in the inquiry, which was carried out with their cooperation. A scale named "attitude toward the referee’s leadership scale," a scale titled "team cohesion scale," and a scale titled "aggressiveness behavioral tendencies scale" were utilised as research instruments. The study showed an inverse association between the cohesiveness measure and the players’ tendency to engage in aggressive conduct. In addition, there may be an inverse relationship between the propensity to engage in violent conduct and the attitude quality associated with leadership in the role of a referee.0